2016
DOI: 10.19136/era.a4n10.756
|View full text |Cite
|
Sign up to set email alerts
|

Aves ribereñas de los ecosistemas costeros de Tuxpan, Veracruz, México

Abstract: Los ambientes ribereños costeros son una fuente de alimento y refugio para una gran diversidad de aves. Por lo anterior, el presente estudio tuvo como objetivo determinar la diversidad, vulnerabilidad, hábitat, estacionalidad y conectividad de aves en cinco ambientes ribereños de Tuxpan, Veracruz. De diciembre de 2012 a octubre de 2014 se realizaron 912 transectos de 1 km de largo y 100 m de ancho en la ribera del río Tuxpan, la laguna de Tampamachoco, los esteros de Tumilco y Jácome, y en la línea costera. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…winter visitors and 17 passerby). The largest migratory component recorded in this study was similar to that reported by Argüelles et al, 6,7 for the coastal environments of Tuxpan (e.g. reefs, river, lagoon, estuaries), which allows us to assume that the region fulfills its function as part of the migration route of the Gulf of Mexico.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…winter visitors and 17 passerby). The largest migratory component recorded in this study was similar to that reported by Argüelles et al, 6,7 for the coastal environments of Tuxpan (e.g. reefs, river, lagoon, estuaries), which allows us to assume that the region fulfills its function as part of the migration route of the Gulf of Mexico.…”
Section: Discussionsupporting
confidence: 90%
“…reefs, river, lagoon, estuaries), which allows us to assume that the region fulfills its function as part of the migration route of the Gulf of Mexico. However, the previous record of avifauna for the northern coastline of Tuxpan mentioned by Argüelles et al, 7 shows that the proportion of resident birds is higher (55.4%) than that of migratory birds (44.6%), which could be indicative of an increase in the migration process during the study period. and significantly with the alpha before ENSO event, while during ENSO within months correlates with t C , indicating that as the effect of ENSO increases so does the number of species, as well as the degree of species replacement increases.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations